A Tsunami Generated by a Strike‐Slip Event: Constraints From GPS and SAR Data on the 2018 Palu Earthquake. Issue 12 (2nd December 2022) - Simons, Wim; Broerse, Taco; Shen, Lin; Kleptsova, Olga; Nijholt, Nicolai; Hooper, Andrew; Pietrzak, Julie; Morishita, Yu; Naeije, Marc; Lhermitte, Stef; Herman, Matthew; Sarsito, Dina Anggreni; et al.
Abstract: A devastating tsunami struck Palu Bay in the wake of the 28 September 2018 M w  = 7.5 Palu earthquake (Sulawesi, Indonesia). With a predominantly strike‐slip mechanism, the question remains whether this unexpected tsunami was generated by the earthquake itself, or rather by earthquake‐induced landslides. In this study we examine the tsunami potential of the co‐seismic deformation. To this end, we present a novel geodetic data set of Global Positioning System and multiple Synthetic Aperture Radar‐derived displacement fields to estimate a 3D co‐seismic surface deformation field. The data reveal a number of fault bends, conforming to our interpretation of the tectonic setting as a transtensional basin. Using a Bayesian framework, we provide robust finite fault solutions of the co‐seismic slip distribution, incorporating several scenarios of tectonically feasible fault orientations below the bay. These finite fault scenarios involve large co‐seismic uplift (>2 m) below the bay due to thrusting on a restraining fault bend that connects the offshore continuation of two parallel onshore fault segments. With the co‐seismic displacement estimates as input we simulate a number of tsunami cases. For most locations for which video‐derived tsunami waveforms are available our models provide a qualitative fit to leading wave arrival times and polarity. The modeled tsunamis explain most of the observed runup. We conclude that co‐seismic deformation was the main driver behind the tsunami that followed the Palu earthquake. Our unique geodetic data set constrains vertical motions of the sea floor, and sheds new light on the tsunamigenesis of strike‐slip faults in transtensional basins. Plain Language Summary: The 28 September Palu earthquake ruptured the Palu‐Koro fault in NW Sulawesi, Indonesia, and was followed by a devastating tsunami in Palu Bay. As the Palu‐Koro fault accommodates mostly horizontal motion, many studies proposed that sub‐marine landslides, rather than the earthquake itself, triggered the tsunami. This study focuses on the contribution of the earthquake to sea floor displacements. We present a unique geodetic data set and estimate a high‐resolution 3D displacement field. The rupture is not a straight feature in the landscape, but rather contains bends. It is near those bends that significant vertical displacements occurred. From the onshore geodetic data we infer another fault bend below Palu Bay. Estimations of fault slip for several scenarios of offshore fault geometries point to a few meters of sea floor uplift. We use these slip models as input for tsunami models, and can qualitatively explain the observations of tsunami runup heights and video‐based tsunami arrival times around Palu Bay. Only at a few locations our models cannot explain tsunami observations, which leaves open the contribution of other possible sources to the tsunami locally. The Palu case underlines the potential importance of fault bends to tsunami generation for similar tectonic settings around the world. Key Points: New Global Positioning System observations as part of a geodetic solution for the full 3D onshore co‐seismic displacements of the 2018 Palu earthquake Below Palu Bay we find a strong indication of dip‐slip on a fault bend, agreeing with the notion of Palu Valley being a transtensional basin A large part of the tsunami, both in terms of arrival times and runup heights, can be explained by co‐seismic slip